Physical deconditioning is the common denominator in both obese and overweight subjects with nonalcoholic steatohepatitis. Issue 3 (24th May 2018) - Argo, C. K.; Stine, J. G.; Henry, Z. H.; Lackner, C.; Patrie, J. T.; Weltman, A. L.; Caldwell, S. H.
Summary: Background: Obesity and decreased physical activity mirror increasing prevalence of nonalcoholic fatty liver disease (NAFLD). Aim: We aimed to investigate associations between aerobic fitness, anthropometrics and disease parameters in patients with nonalcoholic steatohepatitis (NASH). We hypothesised that NASH subjects have lower aerobic power and capacity than untrained, sedentary, normal subjects. Methods: Forty subjects (60% obese, 40% overweight) with biopsy‐confirmed NASH and NAFLD activity score (NAS) ≥4 were enrolled in a clinical trial where anthropometrics, laboratories, liver fat content by MRI, activity, and aerobic fitness by cycle ergometry data were obtained. Results: NASH subjects were significantly deconditioned compared to 148 untrained, sedentary, healthy subjects from our laboratory in aerobic power (VO2peak) (NASH 16.8 ± 6.6 vs control 28.4 ± 10.6 mL/kg/min, P  < 0.0001) and capacity (VO2 at lactate threshold [LT]) (NASH 8.3 ± 2.5 vs control 14.1 ± 5.9 mL/kg/min, P  < 0.0001). NASH subjects' fitness was comparable to the "least fit" tertile of controls: VO2peak [NASH 16.8 ± 6.6 vs "least fit" 17.3 ± 3.3, P  = 0.64]) and VO2 at LT (NASH 8.3 ± 2.5 vs "least fit" 9.3 ± 2.1, P  = 0.31). Fitness was similar in obese compared to overweight subjects (adjusted for gender) and was not correlated with visceral adiposity or NAS. Engaging in dedicated cardiovascular activity correlated with higher VO2peak and VO2peak at LT. Conclusions: Aerobic deconditioning was universally present in NASH subjects. NASH subjects' fitness was similar to our laboratory's "least fit" untrained, sedentary control subjects. Further research investigating NASH patients' ability to improve low baseline aerobic fitness is warranted. Abstract : Linked Content This article is linked to Konerman paper. To view this article visit https://doi.org/10.1111/apt.14915 .